THE REFORMULATION OF PARTIES DOMICILE REQUIREMENTS IN SMALL CLAIM COURT - Rohmatin, Izzatun Tiyas; Syafiuddin, M Nur (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
The requirements of domicile (the same domicile of both parties) in small claim court still become an obstacle in a real application. The purpose of this study is: first, to analyze the linkage between small claim court with the principle of simple, fast, and low-cost. Second, to analyze the realization of the principle of simple, fast, and low cost in both parties' setting domicile in small claim court. Third, to find the formulation of regulation criteria of both parties domicile in small claim court. This research is normative law research, which emphasizes the same domicile requirements on a small claim court. The research results showed that: first, the settlement of the small claim court is the realization of the simple, fast, and low-cost principle. Second, the simple, fast, and low-cost principles are not fully implemented in theÂ arrangement of Â the parties Â domicile. Third, the reformulation of the setting of the domicile of the parties in small claim court is: the parties are domiciled in the same court jurisdiction; If the Plaintiff is not domiciled in the same jurisdiction with the Defendant, the Plaintiff can be called electronically and/ or Plaintiffs can file a lawsuit and appoint a power of attorney, the power of the incidental or representative located in the jurisdiction of domicile of the Defendant with a letter of assignment from the institution of the Plaintiff.